Efficiency of capture of inertia aerosol particles in a periodic cell with a porous cylinder - A.R. Khaziev; Sh.Kh. Zaripov; R.F. Mardanov; A.G. Pilyugin (Учёные записки Казанского университета: Серия Физико-математические науки)
In this study, aerosol flow in circular and rectangular periodic cells of a regular row of porous cylinders is simulated. The hydrodynamic field of the carrier medium flow outside and in the domain of the porous cylinder is described in the approximation of the Stokes–Brinkman model for an incompressible gas. For the model of a circular periodic Kuwabara cell, an analytical solution is obtained; in the case of a rectangular cell, the boundary value problem for the flow stream function is solved numerically using the boundary element method. In the determined velocity fields of the carrier medium, the Lagrangian equations of motion of suspended particles are integrated, and the dependence of the particle capture efficiency as a result of the inertial impact and the interception mechanism on the Stokes number at different cell density and the Darcy number of a porous cylinder is calculated. The results of the calculations are found to be in a good agreement with those from other works carried out using the CFD package. Parametric studies of the efficiency of capture of aerosol particles as a function of the Stokes number for various values of the Darcy number of a porous cylinder, the periodic cell density, and the interception parameter are performed. It is shown that when a porous cylinder is flown around, the particle capture efficiency tends to a non-zero value that increases depending on how high the Darcy number and the density of the periodic cell are. In the region of small Stokes numbers, the capture of particles is provided by both the interception mechanism and the flow through the porous cylinder. A formula is derived for estimating the efficiency of particle trapping under the effect of particle interception on a porous cylinder.